Voting against the party line: how career-related characteristics of Members of Parliament shape their legislative behaviour - Mai, Philipp (2023)
Much of what happens in a parliamentary system of government depends on the ability of party groups and its Members of Parliament (MPs) to act coherently, amongst others the stability and policy-making capability of governing parties or the credibility of opposition parties. Consequently, votes against the party line in parliamentary decisions attract quite some attention, but remain nevertheless a rare phenomenon. This cumulative dissertation aims to explore the individual-level determinants of party unity (and breaches thereof). The overarching question of its constituent articles is to what extent certain components of MPs’ career affect their propensity to vote against the party line in parliament. Theoretically, the articles are based on the understanding that several pathways lead to party unity: division of labour, homogeneity of preferences, loyalty and discipline. Methodologically, each article approximates the effectiveness of a particular pathway by observed MP characteristics and analyses their effect on the probability of vote defections during roll-call votes in the German Bundestag. The observation periods of the articles range from the founding of the Federal Republic of Germany (1949) until 2021. Empirically, the results show that different aspects and stages of MPs’ political career tie in at different points of their decision-making process in the run-up to a parliamentary vote: Concerning the loyalty pathway to unity, MPs’ pre-parliamentary experiences like party offices, on the positive side, or a political socialisation in the former German Democratic Republic, on the negative side, appear to have a stronger impact on their probability of toeing the party line than their seniority in the national parliament. The division of labour pathway favours party-compliant voting behaviour on issues which MPs work on in parliamentary committees and intra-party working groups and thus help shaping the party line. The effectiveness of the discipline pathway to unity is strengthened by currently held offices in parliament and government, but weakened by extensive outside earnings in addition to their parliamentary mandate. Finally, the influence of preferences was tested in the different setting of a ‘free vote’ on organ donation as a morality policy issue. There, MPs’ personal and, to a stronger extent, sociodemographic characteristics of their constituency as well as their party membership are predictors of their voting behaviour. To conclude, the results attribute a distinct explanatory power to all the pathways to unity and underscore the importance of career-related characteristics for MPs’ legislative behaviour. The findings thus have important implications for our understanding of the functioning of parliaments and the complex relationship between voters, parties and their MPs.